Factors influencing audit quality: A systematic literature review - Esmeralda, Angel II P. (Social Sciences Insights Journal, 2025)
This systematic literature review synthesizes empirical research on factors influencing audit quality, examining studies published between 2019 and 2024. The review aims to identify key determinants of audit quality and their relative importance across different contexts. Following the PRISMA 2020 guidelines, this review analyzed 92 peer-reviewed articles from Scopus, Web of Science, and Google Scholar. Studies were categorized based on factor type: auditor-level factors, audit firm-level factors, and external/contextual factors. The review identifies auditor independence, Big 4 affiliation, audit committee effectiveness, and audit tenure as the most consistently studied factors. Big 4 auditors generally demonstrate higher audit quality, though this effect is moderated by client characteristics. Audit committee financial expertise positively influences audit quality through enhanced oversight. Time budget pressure and low audit fees negatively affect audit quality. Emerging themes include the impact of technology adoption and regulatory changes on audit quality. This review provides a comprehensive framework integrating input, process, and output factors affecting audit quality. It offers practical implications for regulators, audit firms, and corporate governance stakeholders while identifying gaps for future research.